The complete mitochondrial genome of the duskytail grouper Epinephelus bleekeri (Serranidae: Epinephelinae). (3rd September 2015) - Wu, Xiaorui; Xie, Zhenzhen; Yang, Lidong; Yang, Huaqiang; Yue, Lei; Hou, Liping; Zhang, Yong; Shu, Hu
Abstract: The complete mitochondrial genome of Epinephelus bleekeri was first presented in this study. It is 17, 227 bp in length, consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a non-coding control region. The overall base composition of the H-strand is 26.32% A, 28.65% T, 28.72% G and 16.31% C. With the exception of ND6 and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. In particular, gene duplication is found on the tRNA-Asp gene, and five tandem repeat of this gene in E. bleekeri is different from most other vertebrates. The control region is rich in A + T (67.12%) and poor in G (14.00%), and tandem repeat sequences are observed in this non-coding region, indicating a useful marker for population genetic studies.